Exotic Biodiversity as Depicted in Vamana Purana - Patil, Dinkarrao Amrutrao (Plantae Scientia, 2024)
After Vedas, Puranas are the literary heritage of India. Vamana Purana is one of the 18 major Puranas. It is divided into 196 sections or chapters with Sanskrit Slokas in which Sanskrit plant names are incorporated. These Sanskrit plant names are equated with valid botanical (Latin) names and their nativities are ascertained to pinpoint plant invasion in ancient period of times on Indian landmass. As many as 16 species pertaining to 16 genera and 14 angiospermic families are revealed. Of these, 04 species are monocotyledons, whereas rest others belong to dicotyledons. Majority of them (11 species) are cultivated, whereas other (05) species run wild on Indian landmass. These are discussed in the light of ancient plant invasion (bioinvasion) in India.